2013
DOI: 10.3389/fmicb.2013.00251
|View full text |Cite
|
Sign up to set email alerts
|

HPV18 E1^E4 is assembled into aggresome-like compartment and involved in sequestration of viral oncoproteins.

Abstract: Papillomavirus is the etiological agent for warts and several squamous carcinomas. Skin cancer induced by cottontail rabbit papillomavirus was the first animal model for virus-induced carcinogenesis. The target organ of the virus infection is stratified epithelium and virus replication is tightly regulated by the differentiation program of the host cell. E1^E4 protein is a viral gene product, and although it is considered to be involved in the control of virus replication, little is known about the biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…Due to their complex composition and functions, virus factories could be contemplated as the living state of viruses . Two main pathways have been identified so far as being responsible for viral factory biogenesis: aggresome formation for DNA viruses and autophagy for RNA viruses (Abernathy et al, 2019;Jackson et al, 2005;Kajitani et al, 2013;Wileman, 2007). Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their complex composition and functions, virus factories could be contemplated as the living state of viruses . Two main pathways have been identified so far as being responsible for viral factory biogenesis: aggresome formation for DNA viruses and autophagy for RNA viruses (Abernathy et al, 2019;Jackson et al, 2005;Kajitani et al, 2013;Wileman, 2007). Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The sequestration of viral proteins into inactive aggregates reduces their activity. Findings by Kajitani et al (2013), showed that human papillomavirus 18 (HPV 18)-infected cells formed aggresome-like compartments at the perinuclear site of the host cells. The major viral oncoproteins E6 and E7 were recruited and sequestrated as an insoluble fraction in these aggresome-like compartments.…”
Section: Cellular Regulatory and Antiviral Effects Of Aggresomes And mentioning
confidence: 99%
“…The major viral oncoproteins E6 and E7 were recruited and sequestrated as an insoluble fraction in these aggresome-like compartments. These compartments, like classical aggresomes, associate with the vimentin cage and are assembled by dynein-dependent retrograde transport along microtubules filaments [55]. The sequestration of viral proteins renders them susceptible to autophagy and results in suppressed viral pathogenesis.…”
Section: Cellular Regulatory and Antiviral Effects Of Aggresomes And mentioning
confidence: 99%
“…Ohsugi et al ( 2013 ) have reported that natural infection status of laboratory mice by murine norovirus. Finally, Kajitani et al ( 2013 ) have described the possible involvement of E1 ∧ E4 protein of human papillomavirus type 18 in its differentiation-dependent life cycle.…”
mentioning
confidence: 99%